eLearning and eMaking: 3D Printing Blurring the Digital and the Physical - Jennifer Loy (Education Sciences, 2014)
This article considers the potential of 3D printing as an eLearning tool for design education and the role of eMaking in bringing together the virtual and the physical in the design studio. eLearning has matured from the basics of lecture capture into sophisticated, interactive learning activities for students. At the same time, laptops and internet enabled phones have made computer-based learning mobile, invading classroom learning, changing communication between students, enabling on the spot research, and making the recording of ideas and activities easier. The barriers between online and offline are becoming blurred in a combined digital and physical learning environment. Three-dimensional printing is part of this unification and can be an empowering learning tool for students, changing their relationship with the virtual and the physical, allowing them to take ideas and thinking from screen to reality and back again in an iterative, connected process, however, from an eLearning point of view it is, more importantly, a transformative technology with the potential to change the relationship of the learner to their learning and the scope and nature of their work. Examples from Griffith Product Design student learning illustrate the potential of eMaking to enhance combined learning in a digital age.